BRANDING PENDIDIKAN VOKASI PARIWISATA TENTANG PERSPEKTIF STAKHOLDER SEKOLAH TINGGI ILMU PARIWISATA MANADO - Nelson Alexander (Jurnal Ilmu Pariwisata, 2024)
The literature on branding of educational institutions is still under development, so far there has been no research that shows branding with tourism universities. This research has a quantitative variation that combines branding with other variables in the context of business organizations. This research aims to explore the formation of branding at vocational higher education institutions in the tourism sector. Data was taken using Focus Group Discussion (FGD) and interviews from stakeholders in the tourism sector. This research uses thematic analysis, namely open coding and axial coding. The research results show that there are main attributes in forming branding, namely identity, alumni, management aspects, quality of human resources and products and competitiveness. With the formation of these branding attributes, this research contributes to measuring the branding of tourism vocational education.